Effect of Oestrus Synchronization and Method of Breeding on Oestrus Duration in Tellicherry Goats - SELVARAJU, M; KATHIRESAN, D; PATTABIRAMAN, S R (The Indian Journal of Animal Reproduction, 2023)
Oestrus was synchronized in 40 Tellicherry  goats by treating intravaginally for 18 days with · Fluorogestone acetate (FGA) or Medroxy  Progesterone acetate (MAP) or controlled Internal Drug Release Device (CIDR) in combination with  600 I.U. Pregnant Mare Serum Gonadotrophin at pessary withdrawal. Twelve goats observed  in natural oestrum were used as control. Each  treatment and control groups were divided equally into N.S. and A.I. groups. At 48 and  60 hours of pessary removal N.S. groups were  bred with intact bucks and A.I. groups were artificially inseminated with frozen semen. In control group, natural service or A.I. was done  twice at an interval of 12 hours after the onset of oestrum. Duration of oestrum in each doe  was measured by using an apronized · buck. Overall oestrus duration was significantly higher  in MAP group than other treatment and control groups. N.S. group of all treatment and control  groups had uniformly shorter oestrus duration than the A.I. group. Hence, it is concluded that  both MAP and natural service had influence on oestrus duration in Tellicherry Goats.
Keywords: Oestrus Synchronization; Tellicherry goats